E-COMMERCE INFORMATION SYSTEM USING TECHNOLOGY ACCEPTANCE MODEL APPROACH - Maichel Ruby Julianto; Benny Daniawan (LPPM STMIK Pringsewu, 2022)
E-commerce websites are one of the most accessed in Indonesia during the covid-19 pandemic. In research conducted for clothing product brands from PT. Mong Kreasi Indonesia, the problem that occurs is the company has not made full use of the information system. The company only uses media social like Instagram and WhatsApp for sales and communication order. Processing and recording of data and transactions are also still manually. The purpose of this research is to design an e-commerce sales information system, that is useful for solving existing problems. To measure the achievement of the designed system, a questionnaire was distributed to the respondents. Total of 70 questionnaires were answered and then tested using the Technology Acceptance Model method using the SMART PLS application. The results is variable Attention to Use on Behavioral Intention to Use has an influence level of 5.063, Perceived Ease of Use on Attention to Use has an influence level of 2.569, Perceived Usefulness on Attention to Use has an influence level of 3.382, and Perceived Usefulness on Behavioral Intention to Use has an influence level of 2.352. Each value is above 1.996, this means each variable has a positive and significant effect in benefits, easy to use, gives satisfaction to users and users has the intention to recommend this system to another.